“I’m elected Chair? Now what?” Helpful Strategies for Newer Chairs - Gian S Pagnucci; Alex Romagnoli; Ethan Krase (Academic Chairpersons Conference Proceedings, 2023)
This session shares concrete strategies for helping department chairs navigate common problems more effectively and efficiently. With attention to managing email, handling complaints, constructing schedules, building relationships, and working with upper administration, the presenters offer practical tips to help newer chairs succeed.
Keywords: practical; email; scheduling; conflicts; management